'An atmosphere of cure': Frederick Mott, shell shock and the Maudsley. Issue 4 (December 2014) - Jones, Edgar
Although recognized as a medical scientist, the work of Frederick Mott as a physician, educator and clinical policymaker has been overshadowed. As a late entrant to the asylum system, Mott questioned established practices of treating mentally-ill patients and campaigned for reform. During World War I, entrusted with the management of the Maudsley neurological section, he sought to raise clinical standards and experimented with a range of therapies designed to treat the most severe or intractable forms of shell shock. While Mott believed that psychiatric disorder was underwritten by inherited characteristics, he did not dismiss the impact of the environment. The diversity of his interests has led to an understatement of his contribution as a physician, not only to the design and founding of the Maudsley Hospital but also to the therapeutic regime practised there during the interwar period.